International Medical Collaboration: Lessons from Cuba - Mauro Castelló González; Reinaldo Pons Vásquez; David Rodriguez Bencomo; Imti Choonara (MDPI AG, 2016)
Over 50,000 Cuban health professionals are currently working overseas in 67 different countries. They work in conjunction with local health professionals. The majority work in primary care in deprived areas. The aim is to reduce morbidity and mortality but also improve health in the long term by training local health professionals, and building both institutions and a structure to deliver health care alongside educating the local population. Cuba is a small, middle-income country. It has, however, made a significant international contribution in relation to medical collaboration. Cuba's international collaboration is based on the principles of social justice and equity for all. It has set an example for other countries to emulate.